Adaptation of the lebanon waterpipe dependence scale to Turkish: a reliability and factor analysis study - Akca, Ali Yunus Emre; Tepedelen, Mehmed Seyda; Yalçınkaya Alkar, Özden (Journal of Dependence, 2020)
Objective: This study aimed to adapt The Lebanon Waterpipe Dependence Scale (LWDS-11) to Turkish in order to facilitate research regarding waterpipe dependence. The LWDS-11 has been constructed and validated as a need for a standardized measure that incorporates not only the assessment of physiological dependence on nicotine but embodies psychosocial factors as well. Method: A sample of N=401 participants responded to the LWDS-11, the Fagerström Test for Nicotine Dependence scale (FTND), and additional socio-demographic related items. Exploratory factor analysis (EFA) has been conducted and outcomes were compared with confirmatory factor analysis (CFA). Assessment of construct and criterion validity was done by the results of the CFA and correlations between the LWDS and the FTND. Results: The sample consisted of N=288 males and N=113 females between the ages 18 and 62.. Computed internal consistency provided a Cronbach’s alpha of .80. Two factors explaining 59% of variance were computed. Conclusion: The outcome of this study has suggested a reliable Turkish assessment tool with validity regarding waterpipe dependence in a Turkish sample.